1984
DOI: 10.1093/infdis/150.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Fimbriation of Haemophilus Species Isolated from the Respiratory Tract of Adults

Abstract: Twenty-two clinical isolates of Haemophilus species were studied within two passages of their original isolation for the presence of fimbriae by negative-staining electron microscopy. Six isolates were identified as fimbriated, including three strains of nontypable Haemophilus influenzae, one strain of Haemophilus parainfluenzae, and two strains of Haemophilus haemolyticus. In fresh isolates of fimbriated strains of nontypable H. influenzae, approximately 40%-50% of cells had fimbriae; after five passages in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0
1

Year Published

1985
1985
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 10 publications
1
12
0
1
Order By: Relevance
“…Pili of respiratory H. influenzae isolates are often not expressed under routine laboratory conditions, but because pilus expression is phase variable, piliated (p ϩ ) variants within populations of nonpiliated (p Ϫ ) bacteria may be identified and enriched for by their adherence to human red blood cells (2). It is likely that the HifA-and HifE-containing pili of the biotype IV strains were in the "off" phase and that we were not able to select for them because they do not bind to, and thus cannot be enriched by, human red blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…Pili of respiratory H. influenzae isolates are often not expressed under routine laboratory conditions, but because pilus expression is phase variable, piliated (p ϩ ) variants within populations of nonpiliated (p Ϫ ) bacteria may be identified and enriched for by their adherence to human red blood cells (2). It is likely that the HifA-and HifE-containing pili of the biotype IV strains were in the "off" phase and that we were not able to select for them because they do not bind to, and thus cannot be enriched by, human red blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of fimbriae has also been demonstrated in other species of the genus Haemophilus (36,37). The reports on the ability of the strains to adhere to epithelial cells and to agglutinate red blood cells have been very contradictory, in part due to the diversity of techniques and the criteria of adherence.…”
Section: Discussionmentioning
confidence: 80%
“…On the other hand, nonfimbriated H. influenzae could adhere and invade into cultured epithelial cells (22). When fresh clinical isolates of H. influenzae were observed by EM, only three of the 15 strains of nontypable H. influenzae were found to be fimbriated and the fimbriae were primarily polar distribution (4). The importance of fimbriae during infection by nontypable H. influenzae needs further investigation.…”
Section: Discussionmentioning
confidence: 96%
“…It is reported that all uncapsulated H. influenzae isolated from the upper respiratory tract are fimbriated, although the degree of fimbriation does not correlate with the ability to adhere to respiratory epithelial cells (5). While another report states that when fresh clinical isolates of H. influenzae were observed under the electron microscope (EM), only three of the 15 strains of nontypable H. influenzae were fimbriated and the fimbriae were mainly in polar distribution (4). The culture condition has a significant effect on the expression of the surface structure of bacteria.…”
mentioning
confidence: 99%